Analisis kapasitas box culvert existing pada pengembangan Bandar Udara Rendani Provinsi Papua Barat - Sinta Afifah K Assem; Falderika (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
Airports serve as transportation facilities that can assist in mobilization and provide access to and from a region. In the context of the development of Rendani Airport in Manokwari, West Papua, an extension of the runway is being carried out. The use of a box culvert as a river channel and foundation for the runway must have sufficient capacity, as it is directly related to the safety of activities at the airport. Therefore, this study aims to calculate the planned flood discharge of the channel to determine the capacity of the installed box culvert. Furthermore, it aims to determine the minimum safe dimensions for the box culvert and assess the safety of the installed dimensions. The analysis used to solve this problem includes frequency distribution analysis, rainfall intensity analysis, the analysis of the runoff coefficient of the catchment area, calculation of the planned flood discharge, and an evaluation of the dimensions of the box culvert. The results of the calculation show that the capacity of the installed box culvert dimensions is 438.4 mÂ³/s, and the planned flood discharge capacity for a 100-year return period is 215.26 mÂ³/s. It can be concluded that the capacity of the installed dimensions is sufficient to meet the planned discharge. Therefore, the minimum existing box size that can be used is 3.1 m x 7 m.